Theory And Practice Of Mediation In Karo Customary Law Community - Gayo, Sabela (Universitas Dharmawangsa, 2026)
This study aims to examine the theory and practice of mediation in the Karo customary law community and see its relevance to the Indonesian national legal system. Karo people are known to have a strong social structure based on kinship and Customs, where mediation is the main mechanism in dispute resolution that emphasizes the value of deliberation and social harmony. This research uses normative juridical method with qualitative approach, supported by literature study and analysis of customary practices that are still in progress in the community. The results showed that mediation of adat Karo not only serves as an instrument of conflict resolution, but also as a means of maintaining social cohesion and strengthening community values. The role of indigenous figures such as kalimbubu, anak beru, and senina is dominant in this process. In the context of national law, customary mediation practices are aligned with restorative justice principles and have the potential to be integrated into formal legal systems. Despite challenges, such as lack of formal recognition and potential conflicts of jurisdiction, adat Karo mediation remains relevant and has strategic value in strengthening local wisdom-based laws.